Caracterização toxicológica e investigação da atividade antifúngica do isoeugenol frente a Penicillium citrinum - Ferreira, Sávio Benvindo (2018)
The loss of food caused by a variety of microorganisms has been recognized as an inconvenience and one of the major concerns of the food industry, mainly because of the economic impact. In addition, with the increasing prevalence of drug-resistant pathogens occurs at a time when the discovery and development of new antimicrobial agents occur slowly. In this way, the present study aims to investigate in vitro and in silico the antifungal activity of isoeugenol against strains Penicillium citrinum and its toxic effects. In order to evaluate the bioactivities and toxicological risk in silico, the online PASS, Molinspiration and Osíris software were used. To investigate the antifungal activity in vitro, the microdilution, checkerboard and ergosterol and sorbitol tests were used. The cytotoxic effect was demonstrated using human erythrocytes. The phytoconstituent had satisfactory oral bioavailability parameters and a reproductive and mutagenic toxicological risk after in silico analysis, but it was not cytotoxic. It presented antifungal action in the strains tested with fungicide effect, causing disturbance in the antifungal plasma membrane. In this way, isoeugenol has been shown to be a possible candidate for biocide and / or antifungal drug for the treatment of fungal infections.